Perbedaan Gender dalam Stres Akademik Menjelang Ujian: Pendekatan Kuantitatif pada Siswa SMA - M. Hubbal Khair (Suria Academic Press, 2026)
Academic stress is a psychological condition frequently experienced by students, particularly during final exam preparation, and may negatively affect mental health and academic performance. This study aimed to examine gender differences in academic stress levels among senior high school students. A comparative quantitative cross-sectional design was employed. The sample consisted of 60 twelfth-grade students of SMAN 1 Padang Sago (30 males, 30 females) selected through purposive sampling. Data were collected using a 20-item Likert-scale academic stress questionnaire with established validity (r > .30) and reliability (α = .87). After meeting assumptions of normality and homogeneity, an independent samples t-test was conducted. The results revealed a significant gender difference in academic stress, with female students reporting higher stress levels than male students, t(58) = 2.41, p = .02, 95% CI [-11.16, -1.04], Cohen’s d = 0.79. The effect size indicates a medium-to-large practical significance. These findings highlight the importance of gender-sensitive interventions in managing academic stress within school settings.